Novel insights into biomarkers of progression in Desmoid tumor - Liu, Baiqi; Sun, Zefang; Zhou, Rui; Shen, Dingcheng; Zhu, Shuai; Chen, Lu; Huang, Gengwen (Frontiers in Oncology, 2023)
Desmoid tumor (DT) is a rare neoplasm characterized by the proliferation of myofibroblastic cells that infiltrates and invades adjacent tissues. Due to its locally aggressive and recurrent nature, DT often causes local symptoms and can be challenging to manage clinically. Therefore, identifying biomarkers that can predict the progression of DT and guide treatment decisions is critical. This review summarizes several biomarkers that have been implicated in active surveillance (AS) and the prediction of postoperative recurrence and attempts to elucidate their underlying mechanisms. Some of these novel markers could provide prognostic value for clinicians, and ultimately help facilitate optimal and accurate therapeutic decisions for DT.